1997
DOI: 10.1159/000201430
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis-Associated Protein in Patients with Celiac Disease: Serum Levels and Immunocytochemical Localization in Small Intestine

Abstract: Since PAP is a stress protein expressed in human pancreas during pancreatitis but also constitutively synthesized in the small intestine, we looked whether its expression would be altered in patients with celiac disease. Serum PAP concentrations were determined consecutively in 54 patients with celiac disease on a free diet (group A), in 47 patients with celiac disease on a gluten-free diet (group B), in 22 patients with other intestinal pathologies but with normal intestinal mucosa (group C), in 14 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In support of findings reported [7,20,25], our experiments clearly showed that PAP/RegIII protein was present in enterocytes at the crypt-villus junction of the ileal mucosa. The protein was not detected in the goblet cells, goblet cell thecae, or Paneth cells.…”
Section: Discussionsupporting
confidence: 91%
“…In support of findings reported [7,20,25], our experiments clearly showed that PAP/RegIII protein was present in enterocytes at the crypt-villus junction of the ileal mucosa. The protein was not detected in the goblet cells, goblet cell thecae, or Paneth cells.…”
Section: Discussionsupporting
confidence: 91%
“…Reg-IIIb mRNA expression was located at the lower villus and upper crypt, suggesting the possibility that Reg-IIIb-expressing cells were relatively newly differentiated or perhaps immature absorptive cells, but not Paneth cells. This profile was partially consistent with that of PAP-I (Reg-IIIbeta in mouse) (Chakraborty et al, 1995b), although in human, hepatocarcinoma-intestinepancreas/pancreatitis-associated protein (HIP/PAP, corresponding to Reg-III) was reportedly located in Paneth cells from patients with celiac disease or inflammatory bowel disease (Carroccio et al, 1997;Gironella et al, 2005). In contrast, Paneth cells did express Reg-IIIc as described in a previous report (Cash et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Also molecules such as ferritin, carbohydrate antigen 19-9, immune complexes and monoclonal antibodies are no improvement on the simple AFP assay [20][21][22][23]. PAP is a protein of pancreatic origin [8] but is also produced by intestinal cells [24] and its gene is activated in the liver during carcinogenesis [10,11]. This study consequently aimed to evaluate its usefulness as a marker of HCC.…”
Section: Discussionmentioning
confidence: 99%